Porous photo-thermal composite material formed by three-dimensional staggered piling and preparation method and application thereof
Through three-dimensional misaligned stacking of porous photothermal composite materials, 3D printing technology is used to build a disassembled structure and coat polyvinyl alcohol solution, which solves the problems of unstable material performance and environmental pollution in seawater desalination technology, and achieves efficient and environmentally friendly Seawater evaporation and desalination effects.
Patent Information
- Application Number
- CN202411395543.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-10
AI Technical Summary
In the existing seawater desalination technology, functional materials have problems such as uncontrollable pore structure, unstable performance, poor salt resistance, and undegradable matrix, resulting in low yield, high cost and serious environmental pollution.
The preparation method of porous photothermal composite materials with three-dimensional misaligned stacking is adopted to construct a disassembled microporous structure through 3D printing technology, combined with polyvinyl alcohol solution coating, improve the capillary effect and solar energy absorption rate of the material, and form high-efficiency seawater evaporation and Materials with desalination ability.
It improves solar energy absorption rate and seawater evaporation efficiency, solves the non-degradation and pollution problems of materials, and achieves an efficient and environmentally friendly seawater desalination effect.
Smart Images

Figure CN119286052A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of material technology, and in particular to a porous photothermal composite material formed by three-dimensional staggered stacking, and a preparation method and application thereof. Background Art
[0002] The increasingly scarce freshwater resources have forced the country to pay more and more attention to green and low-carbon manufacturing and seawater desalination. The desalination of seawater resources has become a promising technology to meet the current demand for fresh water. However, the existing seawater desalination methods (such as seawater freezing method, electrodialysis method, distillation method, reverse osmosis method, and ammonium carbonate ion exchange method) traditional seawater desalination technology generally has technical defects such as large-scale use of chemical reagents, low yield, and high cost. For example, the reverse osmosis membrane used in the reverse osmosis method contains a large amount of polyamide, and its non-degradability has caused great harm to the ocean. In order to improve the performance of traditional seawater desalination technology, functional materials such as photocatalysts, electrocatalysts, photothermal materials, etc. are usually used in thermal desalination technology, membrane-based desalination technology, and other desalination technologies. The application of functional foam materials in seawater desalination technology is very important. These materials significantly improve their own conversion rate to solar energy by filling fillers with high conversion effects on light, thereby achieving a high water evaporation rate and improving the desalination effect on seawater. Among them, commonly used fillers mainly include nano-titanium dioxide, nano-zeolite, graphene, carbon nanotubes, and nano-magnetic particles. However, current functional foam materials generally have problems such as uncontrollable pore structure, unstable performance, poor salt resistance, and non-degradable matrix.
[0003] Therefore, in order to increase the output of seawater desalination technology and promote the green development of seawater desalination technology, it is urgently necessary to develop a new preparation method of porous photothermal composite materials with three-dimensional staggered stacking. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the first aspect of the present invention proposes a method for preparing a porous photothermal composite material formed by three-dimensional staggered stacking, which effectively improves the solar energy absorption rate and combines the capillary effect generated by the three-dimensional multi-through-hole layer to achieve efficient seawater evaporation and desalination.
[0005] The second aspect of the present invention also provides a porous photothermal composite material formed by three-dimensional staggered stacking.
[0006] The third aspect of the present invention also provides an application of a porous photothermal composite material formed by three-dimensional staggered stacking.
[0007] According to a first aspect of the present invention, an embodiment provides a method for preparing a porous photothermal composite material formed by three-dimensional staggered stacking, comprising the following steps:
[0008] S1, constructing a three-dimensional model with a staggered microporous structure in three-dimensional space and performing slicing processing to obtain three-dimensional model data;
[0009] S2, feeding the bio-base material into the material storage bin, importing the three-dimensional model data in step S1 into the 3D printer, and performing dislocation layer-by-layer printing in the vertical direction to obtain a three-dimensional porous photothermal composite material blank;
[0010] S3, coating the polyvinyl alcohol solution on the surface of the blank, and adsorbing and drying it under vacuum conditions; obtaining the porous photothermal composite material formed by three-dimensional dislocation stacking;
[0011] The polyvinyl alcohol solution includes a mixture of polyvinyl alcohol, cuttlefish ink and a carbon material.
[0012] The preparation method according to the embodiment of the present invention has at least the following beneficial effects:
[0013] The present invention adopts bio-based materials which are green, environmentally friendly and easily degradable; it effectively solves the problems of plastic waste pollution, difficulty in recycling and high cost caused by polymer materials used in the seawater desalination process.
[0014] The present invention aims at the problem of low precision of three-dimensional stacking 3D printing technology. By stacking and printing in three-dimensional staggered arrangement, a complex network of stacked structures is stacked inside the three-dimensional space to solve the problem of limited precision of 3D printing equipment, and a porous bio-based composite material with an irregular microporous structure is prepared to have a capillary effect. At the same time, the coating of polyvinyl alcohol solution increases the porosity and reduces the pore size, so that it produces a more obvious capillary effect, which significantly improves the efficiency of water evaporation and desalination.
[0015] Secondly, the polyvinyl alcohol solution in the present invention includes cuttlefish ink and carbon material, and its function is to solidify the cuttlefish ink and carbon material on the surface of the composite material and the through-hole surface through polyvinyl alcohol to improve the solar energy absorption rate and improve the photothermal performance.
[0016] According to some embodiments of the present invention, in step S2, the extrusion speed of the 3D printing is 80 mm / s to 100 mm / s.
[0017] According to some embodiments of the present invention, in step S2, the temperature of the 3D printing is 180°C to 220°C.
[0018] According to some embodiments of the present invention, in step S2, the thickness of the slices printed by 3D printing is 0.127 mm to 0.254 mm.
[0019] According to some embodiments of the present invention, the bio-based substrate includes at least one of starch, wood powder, polyhydroxyalkanoate, polylactic acid, polysuccinic acid or butanediol.
[0020] According to some embodiments of the present invention, the carbon material includes at least one of graphene, carbon nanotubes, carbon black or graphite.
[0021] According to some embodiments of the present invention, the mass ratio of the carbon material, cuttlefish ink, polyvinyl alcohol and water is (1-7): (4-10.5): 10: (72.5-85).
[0022] According to some embodiments of the present invention, in step S3, the drying temperature is 80°C to 100°C.
[0023] According to some embodiments of the present invention, in step S3, the drying time is 8 hours to 12 hours.
[0024] According to some embodiments of the present invention, in step S3, the vacuum degree of the vacuum condition is: 10 -1 Pa~10 -5 Pa.
[0025] According to a second aspect of the present invention, an embodiment provides a porous photothermal composite material formed by three-dimensional staggered stacking, which is prepared by the preparation method described above.
[0026] According to some embodiments of the present invention, the porosity of the porous photothermal composite material formed by three-dimensional staggered stacking is 50% to 75%.
[0027] According to some embodiments of the present invention, the thickness of a single layer of material in the porous photothermal composite material formed by three-dimensional staggered stacking is 0.2 to 1 mm, and the number of layers is 20 to 50. According to some embodiments of the present invention, the aperture of a single layer of through holes formed in the porous photothermal composite material formed by three-dimensional staggered stacking is 0.5 to 1.5 mm; the partial vertical aperture of the multi-layer staggered stacking is 0.01 to 0.1 mm.
[0028] The third aspect of the present invention provides the use of the above-mentioned three-dimensional staggered stacking porous photothermal composite material in the field of preparing seawater desalination materials.
[0029] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0031] Figure 1 2 is a schematic structural diagram of a three-dimensional staggered stacking porous photothermal composite material according to an embodiment of the present invention;
[0032] Figure 2 It is a schematic diagram of the principle of the three-dimensional staggered stacking porous photothermal composite material forming process according to an embodiment of the present invention.
[0033] Figure 3 This is a micrograph of a three-dimensional staggered stacked porous photothermal composite material according to an embodiment of the present invention.
[0034] Figure 4 It is a function diagram of the surface temperature and time under the sunlight of one sun in the photothermal experiment of the embodiments of the present invention and the comparative examples.
[0035] Figure 5 It is a function diagram of the temperature of the surface under the sunlight of one sun and time in the water evaporation experiment of the embodiment of the present invention.
[0036] Figure 6 It is a function diagram of the change of water mass and time in a water evaporation experiment under the sunlight of 1 sun according to an embodiment of the present invention.
[0037] Figure 7 It is a function diagram of the surface temperature and time under the sunlight of one sun in the seawater desalination experiment of the embodiment of the present invention.
[0038] Figure 8 It is a function diagram of the change of water quality and time under the sunlight of 1 sun in the seawater desalination experiment of the embodiment of the present invention. DETAILED DESCRIPTION
[0039] The following are specific embodiments of the present invention, and the technical solutions of the present invention are further described in conjunction with the embodiments, but the present invention is not limited to these embodiments.
[0040] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0041] Example 1
[0042] Example 1 provides a method for preparing a porous photothermal composite material formed by three-dimensional staggered stacking, and the schematic diagram of its preparation principle is as follows: Figure 2 As shown, the steps are as follows:
[0043] S1. Construct a single-layer three-dimensional material with a single-layer thickness of 0.127 mm and a pore size of 1 mm. The single-layer three-dimensional material is staggered with a horizontal stagger value of 0.1 mm in the x-axis direction to form a three-dimensional model of a three-dimensional porous photothermal composite material with a surface area of 30×30 mm;
[0044] S2. Feed the bio-based material into the material storage bin of the 3D printer, then import the three-dimensional porous bio-based composite material virtual model data into the printer, set the 3D printing extrusion speed to 100 mm / s, the printing temperature to 180°C; the thickness of the single-layer slice is 0.127 mm, and perform dislocation layer-by-layer printing in the vertical direction to obtain a three-dimensional dislocation stacking porous photothermal composite material blank;
[0045] S3. Mix graphene, cuttlefish ink, polyvinyl alcohol and deionized water at a mass ratio of 1:5:10:85 at low temperature and evenly coat the mixture on the surface of the initial model. Then place the model in a vacuum pump device for vacuum adsorption, so that the composite is fully and evenly adsorbed on the surface and through holes of the initial model of the three-dimensional porous photothermal composite material. Then, vacuum dry the three-dimensional porous bio-based composite material in a vacuum box for 8 hours at a drying temperature of 80°C. A porous photothermal composite material formed by three-dimensional staggered stacking is obtained.
[0046] The schematic diagram of the structure of the three-dimensional staggered stacking porous photothermal composite material is as follows: Figure 1 As shown, an intricate layer of large through holes and small through holes is formed, which greatly improves the seawater desalination effect through capillary action.
[0047] Example 2
[0048] Example 2 provides a method for preparing a porous photothermal composite material formed by three-dimensional staggered stacking, and the steps are as follows:
[0049] S1. Construct a single-layer three-dimensional material with a single layer thickness of 0.2 mm and a pore size of 1 mm. The vertical pores of some through holes are arranged in a staggered manner according to the horizontal offset value of 0.1 mm in the x-axis direction, forming a three-dimensional model of a three-dimensional staggered stacked porous photothermal composite material with a surface area of 40×30 mm;
[0050] S2, feeding the bio-based material into the material storage bin of the 3D printer, and then importing the three-dimensional porous bio-based composite material virtual model data into the printer, setting the 3D printing extrusion speed to 100 mm / s, the printing temperature to 180°C; the thickness of the single layer slice is 0.127 mm, and the dislocation layer by layer printing is performed in the vertical direction to obtain a three-dimensional dislocation stacking porous photothermal composite material blank;
[0051] S3. Mix graphene, cuttlefish ink, polyvinyl alcohol and deionized water at a mass ratio of 1:5:10:85 at low temperature and evenly coat the mixture on the surface of the initial model. Then place the model in a vacuum pump device for vacuum adsorption, so that the composite is fully and evenly adsorbed on the surface and through holes of the initial model of the three-dimensional porous photothermal composite material. Then, vacuum dry the three-dimensional porous bio-based composite material in a vacuum box for 8 hours at a drying temperature of 80°C. A porous photothermal composite material formed by three-dimensional staggered stacking is obtained.
[0052] Comparative Example 1
[0053] Comparative Example 1 provides a method for preparing a three-dimensional staggered stacking porous photothermal composite material, and its preparation method is the same as that of Example 1, except that step S3 is missing.
[0054] Performance Testing
[0055] The three-dimensional staggered stacking porous photothermal composite materials prepared in Examples 1 and 2 of the present invention were subjected to SEM testing, and the results are as follows: Figure 3 As shown, Figure 3 a, 3b and 3c are micrographs of Example 1 at different magnifications; Figure 3 d, 3e and 3f are micrographs of Example 2 at different magnifications; Figure 3 It can be found that through the staggered stacking molding, the three-dimensional staggered stacking molded porous photothermal composite material forms many fine through holes. Further magnification and observation of the composite material shows that the through holes are arranged in a regular longitudinal staggered manner. At the same time, due to the residual wire attached to the printer head when it moves, a large number of transverse filaments are formed between the through holes, which reduces the pore size and produces a more obvious capillary effect, thereby significantly improving the water evaporation and desalination efficiency.
[0056] The three-dimensional staggered stacking porous photothermal composite materials prepared in Examples 1 to 2 and Comparative Example 1 were subjected to photothermal tests, and the method is as follows:
[0057] 1. Build the photothermal experimental equipment, place the high uniformity integrated xenon lamp light source on the adjustable support frame, and connect the computer and infrared thermal imager;
[0058] 2. Turn on the xenon light source, place the grating of the strong light power meter just below the xenon light source, adjust the grating position so that the strong light power meter displays the current highest value; calculate the optical power density by the five-point method, and continuously adjust the height of the support frame to change the optical power density of the xenon light source reaching the grating until its optical power density is 0.314W / m 2 , which is the light power density under one sun;
[0059] 3. Replace the grating with a foam board that is lower than the grating height of the strong light power meter to ensure that the upper surface of the three-dimensional porous photothermal composite material is highly consistent with the upper surface of the grating; place the three-dimensional misaligned stacked porous photothermal composite material at the position of the grating for experiment, and monitor and process the temperature changes of the three-dimensional misaligned stacked porous photothermal composite material through software.
[0060] Relevant specific data such as Figure 4As shown. Among them, the maximum temperature of the porous photothermal composite material formed by three-dimensional staggered stacking in Example 1 can reach 84.2°C, and the maximum temperature can be stably up to 82°C; the maximum temperature of the porous photothermal composite material formed by three-dimensional staggered stacking in Example 2 can reach 84°C, and the maximum temperature can be stably up to 81.4°C; while the maximum temperature of the three-dimensional staggered stacking porous photothermal composite material in Comparative Example 1 is only 54.5°C, and the maximum temperature can be stably up to 53.5°C;
[0061] The porous photothermal composite material formed by three-dimensional staggered stacking prepared in Examples 1 and 2 was subjected to a water evaporation test, and the method is as follows:
[0062] (1) Build a water evaporation experimental device, place a high-uniform integrated xenon lamp light source on an adjustable support frame, and connect a computer and an infrared thermal imager;
[0063] (2) Turn on the xenon light source, place the grating of the strong light power meter directly below the xenon light source, and adjust the grating position so that the strong light power meter displays the current highest value; calculate the optical power density using the five-point method, and continuously adjust the height of the support frame to change the optical power density of the xenon light source reaching the grating until its optical power density is 0.314W / m 2 , which is the light power density under one sun;
[0064] (3) Prepare a three-dimensional offset stacked porous photothermal composite foam support model, cut the foam board into an outer circle and inner square shape, the outer circle is consistent with the size of the culture dish, the inner square is consistent with the size of the composite material, and the height is consistent with the height of the composite material; put the composite material into the foam support model, and place it in a culture dish filled with water. The upper surfaces of the composite material, the foam support model and the culture dish must be consistent; place a 1 / 10,000 experimental analytical balance directly under the xenon lamp light source and place the culture dish on the balance for experiments. Monitor and process the temperature changes of the three-dimensional porous photothermal composite material through software.
[0065] Relevant specific data such as Figure 5 and Figure 6 As shown, the maximum temperature of the three-dimensional staggered stacking porous photothermal composite material of Example 1 can reach 46.7°C, the maximum stable temperature can reach 46.5°C, and the water evaporation rate under one sun can reach 2.55kg / h·m 2 The maximum temperature of the three-dimensional staggered stacking porous photothermal composite material of Example 2 can reach 47.3°C, the maximum temperature can be stable up to 47°C, and the water evaporation rate under one sun can reach 2.51kg / h·m 2 .
[0066] The three-dimensional staggered stacking porous photothermal composite material prepared in Examples 1 to 2 was subjected to a seawater desalination test. The method was consistent with the water evaporation experiment, except that deionized water and sea salt were mixed in a mass ratio of 1:0.035 to form a seawater solution with a salt content of 35%, simulating real seawater, and replacing the pure water in the water evaporation experiment for the experiment;
[0067] Relevant specific data such as Figure 7 and Figure 8 As shown, the maximum temperature of the porous photothermal composite material formed by three-dimensional staggered stacking in Example 1 can reach 49.1°C, the maximum stable temperature can reach 48°C, and the evaporation rate of seawater under one sun can reach 2.122kg / h·m 2 The maximum temperature of the three-dimensional staggered stacking porous photothermal composite material of Example 2 can reach 50°C, the maximum stable temperature can reach 50.5°C, and the evaporation rate of seawater under one sun can reach 2.133kg / h·m 2 .
[0068] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.
Claims
1. A method for preparing a porous photothermal composite material formed by three-dimensional staggered stacking, characterized in that: The steps include: S1, constructing a three-dimensional model of a microporous structure with staggered arrangement in three-dimensional space and performing slicing processing to obtain three-dimensional model data; S2, feeding the bio-base material into the material storage bin, importing the three-dimensional model data in step S1 into the 3D printer, and performing dislocation layer-by-layer printing in the vertical direction to obtain a three-dimensional porous photothermal composite material blank; S3, coating the polyvinyl alcohol solution on the surface of the three-dimensional porous photothermal composite material blank, and adsorbing and drying it under vacuum conditions; Obtaining the porous photothermal composite material formed by three-dimensional staggered stacking; The polyvinyl alcohol solution includes a mixture of polyvinyl alcohol, cuttlefish ink and a carbon material.
2. The method for preparing a porous photothermal composite material formed by three-dimensional staggered stacking according to claim 1, characterized in that: In step S2, the printing extrusion speed is 80 mm / s to 100 mm / s.
3. The method for preparing the porous photothermal composite material formed by three-dimensional staggered stacking according to claim 1, characterized in that: In step S2, the printing temperature is 180°C to 220°C.
4. The method for preparing a porous photothermal composite material formed by three-dimensional staggered stacking according to claim 1, characterized in that: The bio-based base material includes at least one of starch, wood powder, polyhydroxyalkanoate, polylactic acid, polysuccinic acid or butanediol.
5. The method for preparing a porous photothermal composite material formed by three-dimensional staggered stacking according to claim 1, characterized in that: The carbon material includes at least one of graphene, carbon nanotubes, carbon black or graphite.
6. The method for preparing a porous photothermal composite material formed by three-dimensional staggered stacking according to claim 1, characterized in that: The mass ratio of the carbon material, cuttlefish ink, polyvinyl alcohol and water is (1-7): (4-10.5): 10:(72.5~85)。 7. The method for preparing a porous photothermal composite material formed by three-dimensional staggered stacking according to claim 1, characterized in that: In step S3, the drying temperature is 80°C to 100°C.
8. A porous photothermal composite material formed by three-dimensional staggered stacking, characterized in that: The method is prepared according to any one of claims 1 to 7.
9. The porous photothermal composite material formed by three-dimensional staggered stacking according to claim 8, characterized in that: The porosity of the three-dimensional staggered stacking porous photothermal composite material is 50% to 75%.
10. Use of the porous photothermal composite material formed by three-dimensional staggered stacking according to claim 8 or 9 in the field of preparing seawater desalination materials.